(untitled) (LACCEI, 2024)
The textile sector is positioned as one of the industries that generate a great economic impact in Peru, in addition to being a generator of many sources of work. However, in recent years there has been a low production efficiency in companies related to downtime by operators and the machines used, high material flow, as well as high set up times. In this way, the aforementioned problems generate that the planned production cannot be fulfilled in the established times, causing new expenses due to a misuse of the available resources. In this sense, this article proposes an integrated model that uses Lean Manufacturing tools, including SMED and 5S, hand in hand with TPM and SLP methodologies to increase the operational efficiency. To verify the effectiveness of the of the proposed model, a pilot plan was carried out, giving positive results. In addition, to validate the improvement, a simulation in Arena Software was done, finally reaching an improvement of 11.01% in the index operational efficiency. The contribution proposed in this study can help and guide other SMEs in the textile industry to counteract many of the main problems that afflict them, that the Lean Manufacturing Tools applied together with SLP and TPM methodologies can optimize process from both views of machines and operators, managing to increase efficiency in its operations and a better use of its available resources.